2016
DOI: 10.1111/eth.12578
|View full text |Cite
|
Sign up to set email alerts
|

Defending the Weak: Parental Defense Peaks When Chick Vulnerability is Greatest in the Herring Gull (Larus argentatus)

Abstract: Successful reproduction often depends upon parents providing offspring with resources and protection. In birds, reproductive success can often be enhanced by parents engaging in antipredator behaviors, but these behaviors can be costly. Theoretically, individuals should temporally modify the intensity of nest defense behavior to balance the costs and benefits of current and future reproductive success. More specifically, nest defense should vary throughout a nesting attempt to maximize fitness of the adults. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…It has been shown that various bird species can distinguish between raptors differing in size and then perform appropriate antipredator response behaviours (Evans et al 1993;Templeton et al 2005;Courter and Ritchison 2010). However, many factors, such as habitat, nest stage, sex, nest type and predator location, may influence and cause changes in nest defence behaviour of birds (Burger 1992;Ritchison 1993;Møller et al 2016;Crisologo and Bonter 2017). For example, alarm calling rates increased with the nesting stage in Southern House Wrens (Troglodytes musculus) (Fasanella and Fernández 2009).…”
Section: Open Accessmentioning
confidence: 99%
“…It has been shown that various bird species can distinguish between raptors differing in size and then perform appropriate antipredator response behaviours (Evans et al 1993;Templeton et al 2005;Courter and Ritchison 2010). However, many factors, such as habitat, nest stage, sex, nest type and predator location, may influence and cause changes in nest defence behaviour of birds (Burger 1992;Ritchison 1993;Møller et al 2016;Crisologo and Bonter 2017). For example, alarm calling rates increased with the nesting stage in Southern House Wrens (Troglodytes musculus) (Fasanella and Fernández 2009).…”
Section: Open Accessmentioning
confidence: 99%
“…Semirandomized trial assignments across the seven field researchers guaranteed that each gull experienced only one trial by an individual researcher, none of whom were personally involved in the prior banding or prior year's research on the Appledore gulls. Each focal individual experienced the four trials over a maximum of 5 days (mean = 2.76 days) to minimize the effects of seasonal changes in behavioral response (e.g., Crisologo and Bonter 2016). All trials were conducted between 0630 and 1935 hours and were limited to fair weather conditions.…”
Section: Experimental Trialsmentioning
confidence: 99%
“…In many animals, parental care involves not only provisioning food and protection from inclement weather, but also active nest defence against predators (Clutton-Brock 1991). Parents may prevent nest predation through mobbing, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting departure of a predator from the nest area has a direct benefit (Curio 1978) for offspring survival (Ajie et al 2007;Andersson et al 1980;Lind and Cresswell 2005;Montgomerie and Weatherhead 1988), but driving off a predator is costly in terms of time and energy for the parents (Dugatkin and Godin 1992), and includes the risk of being injured or killed by the predator (King 1999;Mo 2017;Sordahl 1990). Hence, mobbing represents a form of parental investment, and according to life history theory, the level of this investment should depend on its cost-benefit-ratio for the parents (Clutton-Brock 1991). Thus, it is expected that mobbing behaviour varies in relation to a number of internal and external factors associated with the benefits of parental efforts (Caro 2005;Mahr et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation